2007
DOI: 10.1007/s00531-007-0202-2
|View full text |Cite
|
Sign up to set email alerts
|

Separation of rifting and lithospheric folding signatures in the NW-Alpine foreland

Abstract: International audienceThe development of the Alpine mountain belt has been governed by the convergence of the African and European plates since the Late Cretaceous. During the Cenozoic, this orogeny was accompanied with two major kinds of intraplate deformation in the NW-European foreland: (1) the European Cenozoic Rift System (ECRIS), a left-lateral transtensional wrench zone striking NNE-SSW between the western Mediterranean Sea and the Bohemian Massif; (2) long-wavelength lithospheric folds striking NE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 98 publications
(193 reference statements)
0
86
0
6
Order By: Relevance
“…Volcanism accompanied this fragmentation of the upper crust of the WEP at different spots (Bourgeois et al 2007). The last volcanic eruptions occurred in the Eifel (mid-west of Germany) about 11,000 years ago at the Maar of Ulmen and 12,900 years ago at the Lake of Laach volcano (Schmincke 2010).…”
Section: Principal Tectonic Architecturementioning
confidence: 95%
See 1 more Smart Citation
“…Volcanism accompanied this fragmentation of the upper crust of the WEP at different spots (Bourgeois et al 2007). The last volcanic eruptions occurred in the Eifel (mid-west of Germany) about 11,000 years ago at the Maar of Ulmen and 12,900 years ago at the Lake of Laach volcano (Schmincke 2010).…”
Section: Principal Tectonic Architecturementioning
confidence: 95%
“…They appear as grabens and subgrabens (e.g. Lower Rhine, Upper Rhine, Eger, Bresse), activated during the late Eocene with more pronounced rifting starting in late Oligocene and filled with Cenozoic sediments (Ziegler 1994;Geluk et al 1994;Ziegler andDèzes 2006, 2007;Bourgeois et al 2007). Additionally, a system of horsts, blocks and tilted blocks was formed under a still present NW-directed compressional stress field, emerging in the early Miocene and accelerated in the Pliocene (Ziegler andDèzes 2006, 2007).…”
Section: Principal Tectonic Architecturementioning
confidence: 99%
“…(35). Cloetingh and Burov (2011) compiled wavelengths of folded lithosphere, including crustal, mantle and whole lithosphere folding, for 17 regions worldwide, including Central Asia (Burov et al, 1993), central Australia (Lambeck, 1983b), the north-east European platform (Bourgeois et al, 2007), the Tibet/Himalayan syntaxes belt (Shin et al, 2015) and the Indian oceanic lithosphere (McAdoo and Sandwell, 1985;Krishna et al, 2001), and showed that all fold wavelengths are between 40 and 700 km. Not surprisingly, wavelengths for crustal folding are the smallest and wavelengths for whole lithosphere folding are the largest.…”
Section: Lithospheric Foldingmentioning
confidence: 99%
“…If the preceeding assumptions are correct, the subsidence of the MSD and of the entire ED is entirely postLiassic, and probably largely Cenozoic, i.e., comparatively young, as are the structures studied by Dittrich (2014;and references therein). The current stratigraphical inclination of 0.8°may be entirely attributed to the Cenozoic uplift of the RM in the northeastern realm of the study area, also represented as a rift signature by Bourgeois et al (2007). Moreover, the inclination shown in Figure 5b and the subsidence shown in Figure 5a probably are contemporaneous Cenozoic processes.…”
Section: Implications From Tectonics and Stress Fieldmentioning
confidence: 83%
“…On a larger scale, the RM and adjoining areas are deformed and uplifted due to the development and evolution of the ECRIS (represented by the Lower Rhine Graben (LRG) and the Upper Rhine Graben (URG) in Figure 1b) since the Eocene about 40 Ma ago (Bourgeois et al 2007;Demoulin and Hallot 2009;Fuchs et al 1983;Schmincke 2007;Dèzes et al 2004;Ziegler and Dèzes 2007;and references therein). Intensified tectonic activity in the last 700 ka is expressed by the accelerated uplift of the RM and young volcanism in the Eifel region (Demoulin and Hallot 2009;Fuchs et al 1983;Meyer and Stets 2002;Schmincke 2007).…”
Section: Cenozoic Evolutionmentioning
confidence: 99%